Molecular cell biology - Harvey Lodish (W.H. Freeman and Company, 2003)
Molecular Cell Biology provides a clear introduction to the techniques and experiments of scientists past and present, showing how important discoveries led to the formation of the field's key concepts. Since the publication of the Fourth Edition, fundamental principles have emerged from our understanding of molecular cell biology. This Fifth Edition strives to present these principles clearly while providing essential experimental information.